mRNA Expression and Biomarker Responses in Perch at a Biomonitoring Site in the Baltic Sea – Possible Influence of Natural Brominated Chemicals - Förlin, Lars; Asker, Noomi; Töpel, Mats; Österlund, Tobias; Kristiansson, Erik; Parkkonen, Jari; Haglund, Peter; Faxneld, Suzanne; Sturve, Joachim (Frontiers in Marine Science, 2019)
Perch (Perca fluviatilis) has been used in biological effect monitoring in a programme for integrated coastal fish monitoring at the reference site Kvädöfjärden along the Swedish east coast, which is a site characterized by no or minor local anthropogenic influences. Using a set of physiological and biochemical endpoints (i.e., biomarkers), clear time trends for “early warning” signs of impaired health are noted in the perch from this site, possibly as a result of increased baseline pollution. The data sets also show relatively large variations among years. To identify additional temporal variation in biological parameters, global gene transcription studies using RNA sequencing was performed. Perch collected in 2010 and 2014 were selected, as they showed variations in several biomarkers, such as the activity of the detoxification enzyme CYP1A (EROD), the plasma levels of vitellogenin, markers for oxidative stress, white blood cells count and gonad sizes. The RNA sequencing study identified approximately 4800 genes that were differentially expressed. A gene ontology enrichment analysis showed that the differentially expressed genes were involved in biological processes such as complement activation, iron ion homeostasis and cholesterol biosynthetic process. In addition, differences in immune system parameters and responses to the exposure of toxic substances have now been verified in two different biological levels (mRNA and protein) in perch collected in 2010 and 2014. Markedly higher gene expression of the membrane transporter (MATE) and the detoxification enzyme COMT, together with higher concentrations of bioactive naturally produced brominated compounds, such as brominated indoles and carbazoles, seem to indicate that the perch collected in 2014 had been exposed to macro- and microalga blooming to a higher degree than did perch from 2010. These results and the differential expression between the two years in genes related to immune and oxidative stress parameters suggest that attention must be given to algae blooming when elucidating the well-being of the perch at Kvädöfjärden and other Baltic coastal sites.